2020
DOI: 10.3389/fmicb.2020.552566
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Human-Associated Escherichia coli in Wetlands Located in Eastern France

Abstract: Escherichia coli that are present in the rivers are mostly brought by human and animal feces. Contamination occurs mostly through wastewater treatment plant (WWTP) outflows and field amendment with sewage sludge or manure. However, the survival of these isolates in river-associated wetlands remains unknown. Here, we assessed E. coli population structure in low-anthropized wetlands located along three floodplains to identify the major source of contamination of wetlands, whose functioning is different from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Recent work by Flament-Simon et al showed that O:H types O83:H31 and O18:H31 were associated with human source ST372, whereas O4:H31 and O15:H31 were associated with canine source isolates, implicating O:H type as a potential factor in adaptation to each host [16]. Beyond dogs and humans, E. coli ST372 have also been identified globally in diverse wildlife, including migratory birds and fruit bats, wastewater, livestock, drinking water and wetlands [27][28][29][30][31][32]. To the best of our knowledge, a large-scale genomic epidemiological study synthesizing host distribution and defining a clear population structure and the characteristics of different sub-lineages in ST372 is yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Flament-Simon et al showed that O:H types O83:H31 and O18:H31 were associated with human source ST372, whereas O4:H31 and O15:H31 were associated with canine source isolates, implicating O:H type as a potential factor in adaptation to each host [16]. Beyond dogs and humans, E. coli ST372 have also been identified globally in diverse wildlife, including migratory birds and fruit bats, wastewater, livestock, drinking water and wetlands [27][28][29][30][31][32]. To the best of our knowledge, a large-scale genomic epidemiological study synthesizing host distribution and defining a clear population structure and the characteristics of different sub-lineages in ST372 is yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond dogs and humans, E. coli ST372 have also been identified globally in diverse wildlife, including migratory birds and fruit bats, wastewater, livestock, drinking water and wetlands [27–32]. To the best of our knowledge, a large-scale genomic epidemiological study synthesizing host distribution and defining a clear population structure and the characteristics of different sub-lineages in ST372 is yet to be performed.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical isolate cESBL1 belongs to the E. coli phylogroup G (sequencing type (ST) 117), which has been associated with poultry and various mammals as well as severe extra-intestinal diseases in humans and is characterized by high virulence and enhanced antibiotic resistance potential (Clermont et al 2019; Lu et al 2016). The second clinical isolate, cESBL15, is part of the B1 phylogroup in E. coli (ST40), a group adapted to a broad spectrum of hosts but predominantly found in vertebrate animals including humans and frequently harbouring extended-spectrum β-lactamases (Bajaj, Singh, and Virdi 2016; Berthe et al 2013; Clermont et al 2013; Martak et al 2020). In addition, we used three isogenic laboratory strains, E. coli K-12 MG1655 (wild-type, hereafter referred to as MG1655), a variant thereof encoding a chloramphenicol resistance gene ( cat ) inserted into the galK gene locus (Δ galK::cat ) and a chromosomal dTomato marker (hereafter referred to as MG1655+Cm), and another variant carrying a K43R mutation in the ribosomal rpsL gene, providing resistance to streptomycin (hereafter referred to as MG1655+Stm).…”
Section: Methodsmentioning
confidence: 99%
“…Bai et al [17] studied the performance of a constructed wetland and found a 90 % reduction in suspended solids that did not increase when the hydraulic retention time (HRT) was raised from 1 to 3 days. In natural wetlands, high proportions of E. coli isolates can survive in low-anthropized environments [18] while wetland lagoons with floodplains populated with different types of vegetation can both improve the retention times of incoming polluted waters and boost the retention of pollutants that would otherwise reach coastal seawaters. Artificial food web systems using a combination of phytoplankton and zooplankton (with Daphnia) reactors have also been used [19] and are another example of NBS for wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%